Livelihood security assessment of dairy farmers in Nadia district of West Bengal: A microlevel analysis - GARAI, SANCHITA; MAITI, SANJIT; GHOSH, MANOJ; BHAKAT, CHAMPAK; GARAI, SUMAN; KADIAN, K S (The Indian Journal of Animal Sciences, 2021)
Dairying is considered as the most important secondary source of income and employment in India. Therefore, the present study was designed to appraise the livelihood security of the farming community of the Nadia district of West Bengal engaged in dairy farming. Livelihood security index is a composite index which was standardized by considering multi-criterion parameters responsible for livelihood of the dairy farmers, i.e. food and nutrition, economy, health, societal aspect, education and infrastructural resources. In overall, livelihood of the dairy farmers of Nadia district was poor with mean value of 0.42 on a scale of 0 to 1, ranging from 0.22 (Haringhata blocks) to 0.71 (Chakdah block). Comparatively, dairy farmers of Chakdah blocks had higher score in all six components of the livelihood security index than the other studied blocks. Livelihood security index (LSI) is not only highlighting livelihood security generated through dairy farming in Nadia district, but, also emphasizing the necessary policy matters to be intervened for improvement of the livelihood of the millions of resource poor dairy farmers.